Implementation Of The Coordination Functions Of The Maritime And Port Authority In The Governance Of Ahmad Yani Port In Ternate - Tri Sutikno; Nam Rumkel; Muhammad Asykin (JATISWARA, 2026)
This study aims to analyze the implementation of the coordination functions of the Harbor Master’s Office and the Port Authority in the governance of the Ahmad Yani Port area in Ternate, as well as to analyze the factors influencing the effectiveness of these coordination functions in supporting maritime safety and security. This study is motivated by the importance of the coordination functions of the Port Authority as the institution with the highest authority to coordinate customs, immigration, quarantine, and other government agency activities within the port area, as stipulated in Law No. 17 of 2008 on Shipping. However, in practice, the implementation of interagency coordination at Ahmad Yani Port in Ternate still faces various challenges, such as overlapping authorities, weak inter-agency communication, sectoral ego, and limited supporting facilities for port supervision. The urgency of this research lies in the importance of establishing effective, integrated port governance capable of ensuring the safety and security of shipping activities in the North Maluku archipelago. This study employs an empirical legal research method using a legislative approach and a conceptual approach, supported by field data collected through interviews and observations. The research findings indicate that the implementation of the coordination functions of the Harbor Master’s Office and the Port Authority at Ahmad Yani Port in Ternate has been carried out through cross-sectoral coordination with various relevant agencies; however, its effectiveness is still influenced by legal factors, law enforcement factors, infrastructure and facility factors, community factors, and legal culture factors, as outlined by Soerjono Soekanto. The conclusion of this study indicates that strengthening regulatory harmonization, enhancing the professionalism of officials, optimizing supporting facilities, and fostering a culture of inter-agency coordination are crucial steps in improving the effectiveness of port governance. The novelty of this study lies in its empirical focus on the implementation of the coordination functions of the Port Authority in island regions, particularly at Ahmad Yani Port in Ternate, a topic rarely examined in previous research.